Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1515/biol-2016-0011
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genetics related to non-Hodgkin lymphoma

Abstract: Non-Hodgkin lymphoma (NHL) is a serious disease, with a high proportion of mortality. Molecular genetic abnormalities are very common in NHL, but specific characterization in accordance to molecular genetics for lymphoma subtypes is not yet completed. This article summarizes the relationship between B- and T-NHL and molecular genetics. We focus on NHL subtypes and emphasize its features to figure out what is exposed about NHL genetics. The basis of this method is collection of biological specimens for genomic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…The prognostic effect of MYC/BCL 2 coexpression was statistically significant when other factors were considered (e.g., IPI, belonging to the GCB/non-GCB subtype, the presence of c-myc/BCL 2 rearrangements). [12][13][14][15] The author's study of the molecular genetic features of BCL revealed a biological variety and identified several genetic subtypes of this disease, which differ in course and prognosis. Subtypes of B-cell lymphoma develop from genetic disorders in the course of maturation of B-lymphocytes and are described by blocking apoptosis, impaired regulation of BCL 2, loss of function of BCL 6, deletion of p53 and increased cell proliferation, impaired regulation of c-myc.…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic effect of MYC/BCL 2 coexpression was statistically significant when other factors were considered (e.g., IPI, belonging to the GCB/non-GCB subtype, the presence of c-myc/BCL 2 rearrangements). [12][13][14][15] The author's study of the molecular genetic features of BCL revealed a biological variety and identified several genetic subtypes of this disease, which differ in course and prognosis. Subtypes of B-cell lymphoma develop from genetic disorders in the course of maturation of B-lymphocytes and are described by blocking apoptosis, impaired regulation of BCL 2, loss of function of BCL 6, deletion of p53 and increased cell proliferation, impaired regulation of c-myc.…”
Section: Discussionmentioning
confidence: 99%